2001
DOI: 10.1021/jo0100392
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Highly Chemo- and Regioselective Formal [2 + 2 + 2] Sequential Cycloaddition of Alkynes:  A Renaissance of the Well Known Trimerization Reaction?

Abstract: A new concept of highly chemo- and regioselective formation of the benzene ring by a palladium-catalyzed formal [2 + 2 + 2] sequential intermolecular trimerization of alkynes is proposed. Homodimerization of terminal alkynes and subsequent [4 + 2] benzannulation with diynes gives tetrasubstituted benzenes in moderate to good yields. The introduction of two different alkynes (terminal and internal) in the first step of the sequence allows for construction of pentasubstituted benzenes from three different acycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 24 publications
0
57
0
Order By: Relevance
“…[62] The cyclotrimerization of a diyne species with a benzyne precursor was subjected to catalysis by [NiA C H T U N G T R E N N U N G (acac 3 complex was found to be most effective, which was utilized in the total synthesis of taiwanins C and E (Scheme 38). Other examples of Pd catalysis in the synthesis of benzene derivatives include the use of PdA C H T U N G T R E N N U N G (PPh 3 ) 4 to form 1,2,3,5-tetrasubstituted benzenes, [63] the Pd 2 A C H T U N G T R E N N U N G (dba) 3 -catalyzed cycloaddition of benzyne to 1,6-diynes to afford benzo [b]fluorenones, [64] and the PdCl 2 A C H T U N G T R E N N U N G (PPh 3 ) 2 -mediated co-cyclotrimerization of benzynes with bicyclic alkenes to form anellated 9,10-dihydrophenanthrene derivatives. [65] These reports have been reviewed earlier.…”
Section: Synthesis Of Substituted Thiopyridones and Dithiopyronesmentioning
confidence: 99%
“…[62] The cyclotrimerization of a diyne species with a benzyne precursor was subjected to catalysis by [NiA C H T U N G T R E N N U N G (acac 3 complex was found to be most effective, which was utilized in the total synthesis of taiwanins C and E (Scheme 38). Other examples of Pd catalysis in the synthesis of benzene derivatives include the use of PdA C H T U N G T R E N N U N G (PPh 3 ) 4 to form 1,2,3,5-tetrasubstituted benzenes, [63] the Pd 2 A C H T U N G T R E N N U N G (dba) 3 -catalyzed cycloaddition of benzyne to 1,6-diynes to afford benzo [b]fluorenones, [64] and the PdCl 2 A C H T U N G T R E N N U N G (PPh 3 ) 2 -mediated co-cyclotrimerization of benzynes with bicyclic alkenes to form anellated 9,10-dihydrophenanthrene derivatives. [65] These reports have been reviewed earlier.…”
Section: Synthesis Of Substituted Thiopyridones and Dithiopyronesmentioning
confidence: 99%
“…(2) in Scheme 4]. [14][15][16][17] In this work, we found that three triple bonds out of four [shown in Eq. (3) in Scheme 4] could be highly selectively integrated into a benzene derivative; one of the triple bonds in bis(alkynyl)siScheme 2.…”
Section: Resultsmentioning
confidence: 95%
“…Many examples of effective run of the process in the presence of transition metal complexes have been described. Catalytic activity in the process has been reported to be shown by complexes of such metals as palladium [4,[7][8][9][10][11][12][13], rhodium [14][15][16][17][18][19], ruthenium [20][21][22][23][24][25][26][27][28][29], nickel [30], iridium [31][32][33], osmium [34,35], iron [36] and the f-block metals [37][38][39]. However, a highly selective synthesis of conjugated enynes by dimerization is still a challenging process.…”
Section: Introductionmentioning
confidence: 99%